INNOVATION MODEL FOR DEVELOPMENT OF AN EDU-TOURISM AREA BASED ON TAPIS CLOTH FOR THE TAPIS JEJAMA KHAM WOMEN'S GROUP IN PESAWARAN REGENCY, LAMPUNG PROVINCE - Farida, Ida; Purnomo, Agus; Juwita, Masayu Nila; Ardiansyah, Muhammad (Universitas Padjadjaran, 2024)
This research aims to determine the strategy for implementing an innovation model for developing educational tourism areas based on filter cloth to increase product sales by utilizing available resources. The innovation model is developed through developing a master plan for an edu-tourism area based on Tapis by inventorying the potentials in the village of Negeri Katon Pesawaran. This research used the Soft System Methodology (SSM) method. SSM is a systemic approach to dealing with complex and less structured situations. In developing a Tapis cloth-based edu-tourism area by the Tapis Jejama Kham Women's Group in Pesawaran Regency, SSM can be used to understand the various aspects involved and develop a comprehensive solution. The steps of this research are needs analysis, testing of the innovation model, module development, and reporting. Literature studies were carried out on related documents such as regulations, book references, and updated journals. Meanwhile, interviews were conducted with several informants, such as the Tapis Jejama Kham women's group, cultural activists, the tourism and creative economy department of Lampung Province, and local communities of Negeri Katon Village. The preliminary findings of this study show that there are a lot of potential natural resources and human resources as well as cultural heritage in Negeri Katon village, Pesawaran district, which has not been managed optimally, and there is a lack of public awareness regarding the management of existing tourism potential. This research has attempted to contribute to the creation of a regional innovation model of the edu-tourism area based on tapis cloth for the tapis jejama women’s group in Pesawaran District, Lampung Province and the creation of Intellectual Property Rights in the form of a Master Plan for the model of edu-tourism area in the Negeri Katon subdistrict.